EU questionnaire to screen for obstructive sleep apnoea validated in Slovakia - Feketeová, Eva; Mucska, Imrich; Klobučníková, Katarína; Grešová, Soňa; Štimmelová, Judita; Paraničová, Ivana; Trojová, Ivana; Rosenberger, Jaroslav; Rimárová, Kvetoslava; Dorko, Erik (Central European Journal of Public Health, 2018)
OBJECTIVE: Obstructive sleep apnoea syndrome (OSAS) associated with daytime sleepiness (DS) contributes to a higher incidence of motor vehicle accidents. Validation of fitness to drive in driving license applicants, with special concern regarding OSAS accompanied by excessive DS, became mandatory under new EU legislation in January 2016. The aim of the study was to translate and validate the recommended questionnaire to screen for OSAS (Q-OSAS) in the Slovak population. No data on any Q-OSAS validation has previously been published. METHODS: The translated Q-OSAS was administered to 311 Slovak patients prior to a planned overnight polysomnography. The diagnostic accuracy of the Q-OSAS in OSAS with an apnoea-hypopnoea index of 15 or more/h of sleep was evaluated by calculating the area under the ROC curve. RESULTS: The sensitivity and specificity of the cut-off at 10 points for the Q-OSAS was 57% and 67%, respectively, with an increase of sensitivity and a decrease of specificity with a lowering of the cut-off values. Excluding the Epworth Sleepiness Scale (ESS) score from the final statistics yielded the best sensitivity (77%), specificity (50%), and an area under the ROC curve (0.637) for the cut-off value of 8 points (an equivalent of 10 points with the full version of the Q-OSAS). CONCLUSION: The Q-OSAS is an appropriate screening tool to facilitate the screening of subjects potentially at risk from moderate and severe OSAS. A modified two-step interpretation of the Q-OSAS in Slovakia yielded the best sensitivity, and in the future could promote evaluation of sleepiness in sleep and wake disorders other than OSAS for fitness to drive.
Keywords: Sleep; Translating; překládání; lidé; Mass Screening; Reproducibility of Results; Polysomnography; plošný screening; průzkumy a dotazníky; reprodukovatelnost výsledků; Slovenská republika; polysomnografie; Sleep Apnea, Obstructive; Surveys and Questionnaires; Humans; psychometrie; spánek; obstrukční spánková apnoe; Psychometrics; Slovakia